Emerging Role of PD-1/PD-L1 Inhibitors in Chronic Liver Diseases - Singh, Vishakha; Khurana, Amit; Allawadhi, Prince; Banothu, Anil Kumar; Bharani, Kala Kumar; Weiskirchen, Ralf (Frontiers in Pharmacology, 2021)
Programmed cell death protein 1 (PD-1)/PD-ligand (L)1, the immune checkpoint inhibitors have emerged as a promising strategy for the treatment of various diseases including chronic liver diseases (CLDs) such as hepatitis, liver injury and hepatocellular carcinoma (HCC). The role of PD-1/PD-L1 has been widely inspected in the treatment of viral hepatitis and HCC. PD-1 is known to play a crucial role in inhibiting immunological responses and stimulates self-tolerance by regulating the T-cell activity. Further, it promotes apoptosis of antigen-specific T-cells while preventing apoptosis of Treg cells. PD-L1 is a trans-membrane protein which is recognized as a co-inhibitory factor of immunological responses. Both, PD-1 and PD-L1 function together to downregulate the proliferation of PD-1 positive cells, suppress the expression of cytokines and stimulate apoptosis. Owing to the importance PD-1/PD-L1 signaling, this review aims to summarize the potential of PD-1/PD-L1 inhibitors in CLDs along with toxicities associated with them. We have enlisted some of the important roles of PD-1/PD-L1 in CLDs, the clinically approved products and the pipelines of drugs under clinical evaluation.